The Setting Questionnaire for the Ayahuasca Experience: Questionnaire Development and Internal Structure - Pontual, Alexandre Augusto de Deus; Tófoli, Luís Fernando; Collares, Carlos Fernando; Ramaekers, Johannes G.; Corradi-Webster, Clarissa Mendonça (Frontiers in Psychology, 2021)
The growing interest in research on psychedelic consumption in naturalistic contexts and their possible medical and therapeutic benefits requires assessment of the relationships between the substance and the individual who consumes it (set) and its context of use (setting). This study provides a novel measurement scale for the setting of Ayahuasca consumption, the Setting Questionnaire for the Ayahuasca Experience (SQAE), and examines its psychometric properties. Construction of the scale began with a literature review, followed by interviews on 19 Ayahuasca users from different backgrounds and different consumption experience, and an online survey for quantitative data collection (n = 2994). Exploratory Graph Analysis (EGA) was used to investigate the questionnaire’s dimensional structure with (n = 1497, half of the sample), and multidimensional item response theory (MIRT) was used to compare the fit of the theoretical dimensions with the EGA proposed dimensions (n = 1497, independent other half). EGA identified six dimensions, which corresponded partially to the theorized model (Leadership, Decoration, Infrastructure, Comfort, Instruction and Social). The MIRT comparison found that the proposed theoretical model fit significantly better than the EGA model, providing support for the former (χ2/df = 1,967; CFI = 0,972; TLI = 0,969; RMSEA = 0,059; WRMR = 1,087). Our findings present evidence of validity of this instrument, justifying its use for future research on the influence of the setting during the ayahuasca experience. Its findings may provide a basis for expanding the settings investigated in the use of psychedelics in general.